Craspedostauros alatus sp. nov., a new diatom (Bacillariophyta) species found on museum sea turtle specimens. Issue 2 (3rd April 2018) - Majewska, Roksana; Ashworth, Matt P.; Lazo-Wasem, Eric; Robinson, Nathan J.; Rojas, Lourdes; Van de Vijver, Bart; Pinou, Theodora
Abstract : Several populations of a new Craspedostauros species were observed on museum specimens of juvenile green turtle and Kemp's ridleys collected from Long Island Beach, New York, USA. The new taxon, Craspedostauros alatus Majewska & Ashworth sp. nov., exhibits a distinctive set of morphological features typical of the genus, including cribrate areolae, a stauros narrower than the fascia, multiple doubly perforated girdle bands, and two fore and aft chloroplasts, but clearly differs from all known Craspedostauros species in possessing partially fused proximal helictoglossae forming an internal thickening with a shallow central cavity, distinctive external wing-like silica flaps near the apices, and a combination of valve dimensions and stria density not observed in other taxa. The same taxon was identified in the NCMA culture collection (strain CCMP120), isolated in 1967 from a sample collected from the equatorial upwelling zone in the Pacific Ocean. Nine samples from three sea turtle species were collected from the same location (Long Island Beach). Statistical analyses suggested that the epizoic diatom flora composition was not affected by the collection season but differed among sea turtle species. The most significant difference was observed between the samples with and without C. alatus . Samples with C. alatus were always dominated by Achnanthes elongata and Berkeleya cf. rutilans, while those lacking the new taxon were characterized by remarkably higher contributions of epizoic Poulinea species. This observation suggests that the microhabitat provided by each sea turtle differs among specimens, which may be related to the different stages of biofilm development on the host sea turtle. Additionally, the value of zoological museum collections for epizoic diatom surveys is briefly discussed.